Just a Fragment of Undescribed Diversity: Twenty New Oriental and Palearctic Species of Sciaroidea (Diptera), including DNA Sequence Data and Two New Fossil Genera - Ševčík, Jan; Hippa, Heikki; Burdíková, Nikola (Insects, 2021)
The following 17 extant new species of Sciaroidea (Diptera: Bibionomorpha) are described: Bolitophila nikolae Ševčík sp. nov. (Bolitophilidae, Taiwan), Catocha jingfui sp. nov. (Cecidomyiidae, Taiwan), Catocha manmiaoe sp. nov. (Cecidomyiidae, Taiwan), Catocha shengfengi sp. nov. (Cecidomyiidae, Taiwan), Planetella taiwanensis sp. nov. (Cecidomyiidae, Taiwan), Diadocidia pseudospinusola sp. nov. (Diadocidiidae, Taiwan), Asioditomyia bruneicola sp. nov. (Ditomyiidae, Brunei), Asioditomyia lacii sp. nov. (Ditomyiidae, Taiwan), Ditomyia asiatica sp. nov. (Ditomyiidae, Thailand), Chetoneura davidi sp. nov. (Keroplatidae, Brunei), Euceroplatus mantici sp. nov. (Keroplatidae, Thailand), Setostylus fangshuoi sp. nov. (Keroplatidae, Taiwan), Platyceridion yunfui sp. nov. (Keroplatidae, Hainan), Terocelion adami sp. nov. (Keroplatidae, Taiwan), Hadroneura martini sp. nov. (Mycetophilidae, Taiwan), Paratinia furcata sp. nov. (Mycetophilidae, Czech Republic, Slovakia), and Nepaletricha sikorai sp. nov. (Sciaroidea incertae sedis, Thailand). Two new genera are described from the mid-Cretaceous Burmese amber, Burmasymmerus gen. nov. (Ditomyiidae, type species Burmasymmerus korneliae sp. nov., including also B. wieslawi sp. nov.), representing the first record of the family Ditomyiidae from the Mesozoic, and Burmatricha gen. nov. (Sciaroidea incertae sedis, type species Burmatricha mesozoica sp. nov.). Molecular phylogeny of Ditomyiidae, based on two DNA markers (28S, COI), as well as that of Catocha Haliday, 1833, based on the mitochondrial COI and 16S fragments, are also presented.
Keywords: palearctic region; taxonomy; oriental region; fungus gnats; DNA barcoding; Bibionomorpha; Diptera